Design and Implementation of a Web-based Integrated Marine and Atmospheric Geographical Information System (International Journal of Engineering and Computer Science, 2018)
Traditional geographic information systems and modeling systems have specific limitations in marine and atmospheric research area, such as using ocean mode analysis method to deal with massive remote sensing data. To overcome such limitations, in this paper, a web-based distributed geographical information system for the automatical execution of marine and atmospheric research simulation and analysis is presented. It integrates a group of individual applications by combining marine and atmospheric data acquisition, storage, retrieval, analysis and visualization functions. The system exhibits a modular, extensible, and scalable architecture. The well-established three-tier architecture is exploited to build the user interface. An execution model and distributed system techniques are deployed to support the high efficiency execution of user’s request. The user interface of the system is implemented in C#, the distributed execution system is implemented based on Web Services technique. Major advances are inclusions of models from expert knowledge(execution model) and techniques to get high performance(distributed system).